Evaluation of the Implementation of the Procurement of Government Goods/Services In Gorontalo Regency - Pertiwi Kadir; Meimoon Ibrahim; Irwan Halid (LP2M Universitas Bina Mandiri Gorontalo, 2021)
This study aims to: (1) determine and analyze the implementation of the government'sprocurement of goods/services in Gorontalo Regency. (2) To find out and analyze whatfactors influence the process of implementing government procurement of goods/services inGorontalo RegencyThis research is a research with a qualitative descriptive approach, namely examining,analyzing and decrypting the data.The results showed that (1) the working group had carried out explanations, but theworking group's readiness in providing initial explanations and in answering questions fromparticipants was still not optimal, because there were still working groups that providedinitial explanations that had passed the allotted time. (2) the evaluation of the bid documentshas followed the existing regulations, however, due to frequent changes in regulations, theunderstanding of the working group may differ from one another. Because there are workinggroups that can quickly adjust existing regulations, some are not. (3) Proof of qualification isfollowed in accordance with existing regulations. It's just that the timeliness of theprospective provider is still lacking because it always comes at the time of proving thequalifications will end. (4) The stage of refutation of the working group tries to provideanswers to potential providers in a good, relevant, and transparent manner. It's just that thebidders are dissatisfied. Because they didn't win, they use the rebuttal route to express theirdissatisfaction. (5) Human resources and facilities and infrastructure are sufficient. However,if there are a large number of packages being tendered, the working group will ask for theassistance of personnel from other OPDs to become an election working group. (6) social,political and economic factors greatly influence the implementation of governmentprocurement of goods/services. From an economic point of view, the tender process is thestarting point for selecting business actors. Business actors will compete and will takeadvantage of existing resources and of course will increase the economic income of thecommunity. Judging from the social conditions, the community can work or be directlyinvolved in the project. If politics is very influential, but the working group must still beguided by the existing rules. So, there will be considerations that must be placed on the rulesin the procurement of goods/services. (7) the disposition factor can affect the process ofimplementing government procurement of goods/services in the provider selection stage, it'sjust that the working group's attitude must always be able to understand the existing rules, sothat everything can be adjusted